Influence of Chicken EggShell Powder Ratio with Coarse Rice Husk on Methyl Orange Removal from Aqueous Solution - Haqiqi, Embun Rachma; Hikmawati, Dwi Ima (Universitas PGRI Madiun, 2019)
Chicken eggshell and rice husk waste have been succesfully used as a potential adsorbent of methyl orange (MO). In this study, after the washing and drying process, chicken eggshells were mashed while the rice husk was left intact. Chicken eggshell powder and coarse rice husk were combined and varied its composition ratio by 3: 1, 2: 1, 1: 1, 1: 2, and 1: 3. The adsorption process of 50 mL MO 20 ppm in aqueous solution with 11 grams of adsorbent was measured using the UV-Vis Spectrophotometer Genesys 20 at 465 nm. Based on the results of the study, the adsorbent with a variation of 1: 1 in ratio was able to adsorb MO from the solution up to 27.70% within 60 minutes.